2022
DOI: 10.1002/ehf2.13779
|View full text |Cite|
|
Sign up to set email alerts
|

Echocardiographically defined haemodynamic categorization predicts prognosis in ambulatory heart failure patients treated with sacubitril/valsartan

Abstract: Aim Echo-derived haemodynamic classification, based on forward-flow and left ventricular (LV) filling pressure (LVFP) correlates, has been proposed to phenotype patients with heart failure and reduced ejection fraction (HFrEF). To assess the prognostic relevance of baseline echocardiographically defined haemodynamic profile in ambulatory HFrEF patients before starting sacubitril/valsartan. Methods and resultsIn our multicentre, open-label study, HFrEF outpatients were classified into 4 groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Therefore, based on the pharmacological mechanisms of sacubitril-valsartan, it can be presumed that sacubitril-valsartan could also prevent or modify atrial remodeling through similar or even stronger effects as ACEI/ARB monotherapy. More recently, Carluccio et al assessed changes in echocardiographically derived hemodynamic profiles induced by sacubitril-valsartan in a large consecutive series of patients with HF ( 36 , 37 ). They found that an important role of sacubitril-valsartan on improvement cardiovascular hemodynamics including cardiac output and left ventricular filling pressure ( 36 , 37 ), which might provide new insights into the underlying mechanism of effects of sacubitril-valsartan on restoration and maintenance of sinus rhythm for persistent AF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the pharmacological mechanisms of sacubitril-valsartan, it can be presumed that sacubitril-valsartan could also prevent or modify atrial remodeling through similar or even stronger effects as ACEI/ARB monotherapy. More recently, Carluccio et al assessed changes in echocardiographically derived hemodynamic profiles induced by sacubitril-valsartan in a large consecutive series of patients with HF ( 36 , 37 ). They found that an important role of sacubitril-valsartan on improvement cardiovascular hemodynamics including cardiac output and left ventricular filling pressure ( 36 , 37 ), which might provide new insights into the underlying mechanism of effects of sacubitril-valsartan on restoration and maintenance of sinus rhythm for persistent AF.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its modest correlations with outcomes in HFpEF ( 33 ), E/e’ ratio displays prominent specificity for identifying patients with increased LV filling pressure ( 34 ). A recent study conducted by Dini et al ( 35 ), which involved 727 outpatients with HFrEF, demonstrated that a functional hemodynamic stratification approach based on a cardiac index (using 2.0 L/min/m 2 as the threshold for low output) and E/e’ ratio (using a value ≥ 15 as a marker of increased LV filling pressure) is useful in predicting survival. A similar pathophysiological stratification approach based on an assessment of cardiac hemodynamics (ventricular forward flow and filling pressure) has also been proposed in patients with cardiogenic shock ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…HFrEF patients with varied risk profiles are identified using echocardiographic hemodynamic classification. Sacubitril/valsartan improves outcome across hemodynamic profiles in real-world HFrEF outpatients (52). Treatment with low doses of ARNI might successfully improve cardiac function in hemodialysis (HD) patients with heart failure and hypotension.…”
Section: Current Studiesmentioning
confidence: 99%